Indications of recent warm and dry summers' impact on private wells for drinking-water supply in Germany: a review of press articles. (13th December 2021) - Rickert, B.; Görnt, A.; Vogelsang, L.; Ruhl, A. S.
Abstract: Climatic changes lead to seasonal droughts with declining groundwater levels, and – especially in rural regions – private wells in the upper aquifer might fall dry. However, only limited information and no systematic administrative reporting of the extent are available for Germany yet. Therefore, a systematic analysis of newspaper articles as a promising source of information was conducted for the extraordinarily hot summers of 2018, 2019 and 2020. The results of the database searches were analysed with respect to frequency and local and regional hotspots, relations to climatic data, extent of the reported dry-fallings and emergency water supply. The analysis indicates hotspots particularly for the federal states of Saxony, where a subsidy programme for connecting to the public water supply was reissued in 2019, for Bavaria and North Rhine-Westphalia. Emergency supply was realised through various approaches. It was partly required until the winter months and did not always have drinking-water quality. As private wells are particularly vulnerable to the effects of climate change, their operators should be involved as a stakeholder group in future discussions about allocating water resources to increasingly competing uses in periods of scarcity. HIGHLIGHTS: An analysis of newspaper articles showed the impacts of warm and dry summers on private wells and regional hot spots in Germany. Private wells are particularly vulnerable to the effects of climate change. Emergency water supply was partly required into the winter months. Increased willingness to connect to the central water supply exists among operators of private wells, and a subsidy programme was reissued.